ESTUDO DA CORROSÃO MICROBIOLÓGICA NO AÇO INOXIDÁVEL 316 EM Na2SO4 0,5 mol Lˉ¹ - Moraes, Jeferson Egner de (2009)
Steel AISI 316 is resistant to the corrosion, making possible its application in systems of water distribution, industries of paper, petroliferous and nourishing. Its durability must to the high purport of chromium and nickel; therefore these elements form an auto-passivante oxide layer, conferring resistance to it environmental oxidants. The durability of steel AISI 316 has diminished, due to action of existing microorganisms in environmental industrial, where it has the seaweed increase, fungus and bacterium. In the present work it was studied the influence of Escherichia coli in the corrosion of steel AISI 316, in environment Na2SO4 0,5 mol Lˉ¹. The techniques open circuit potential had been used (OCP), Linear Sweep Voltametry (LSV), spectroscopy of electrochemical impedance (SEI), optic microscopy (OM) and cyclic voltametry (CV) and scanning electron microscopy (SEM). The results gotten in the LSV,in pH 7 had disclosed that steel AISI 316 is passive in until 0,95V/ESM. It was verified that in the transpassive region the solution with 0,1% of E. coli minimized the current density, two to formation of biofilm, however when the concentration of was increased. E. coli for 1% and 10%, this was noticed that the current density increases significantly, if it must to the fact have the to detach of biofilm of the surface of the metal. Although to have occurred a augmentation of the anodic potential in the way in pH 6, and in pH the 8, the linear sweep voltametry in the three values of pH had demonstrated similar behaviors. The SEI had confirmed that the resistance of steel AISI 316 diminishes with the addition of the concentration of bacteria. The micrographs had disclosed the formation of biofilm on the surface of the metal, as well as the sprouting of corrosion, proven for cyclic voltametry. The SEM elucidated that the type of corrosion that stainless steel AISI 316 suffers in the presence from the E. coli is located (pitting). The region where biofilm is adhered becomes little oxygenation, making with that the steel loses the capacity to form the auto-passivante oxide layer, becoming susceptible the corrosion.